Risk factors for burnout syndrome in nurses at a public hospital in Mossoró/RN, Brazil - Bruna Nogueira Alves; Camilla Cavalcante Freitas; Gabriel Sousa Rocha; Marco Aurelio Freire (Hospital de Clínicas de Itajubá, 2023)
Objective: To evaluate the risk factors for Burnout syndrome rise in nurses at the Tarcisio de Vasconcelos Maia Regional Hospital in Mossoró/RN. Methods: Exploratory, descriptive, prospective, quantitative and cross-sectional study in 119 nurses from March to September 2022, carried out under license from the Research Ethics Committee of UERN (#4,915,042). A questionnaire with socio-organizational information and the Copenhagen Burnout Inventory containing 19 items that reflect professional burnout, in a scale categorized as low, intermediate and high burnout, were applied. Results:  Most of the interviewees were female (81%), with an average of 36.4 years old, married (70%), with specialization in the area (74%), and two jobs (59%). It was possible to identify a higher prevalence of high levels of personal burnout (44%), and intermediate levels of work-related burnout (52%), and client-related burnout (50%). A strong positive correlation between the number of employment contracts for the dimensions personal (r=0.74, p=0.03) and work-related burnout (r=0.81, p=0.02), a strong positive correlation between workload and personal burnout (r=0.68, p=0.04), and a moderate positive correlation between workload and work-related burnout (r=0.53, p=0.04) were identified. Conclusions: Exposure to long workload resulted in increased levels of both physical and psychic exhaustion in nurses, negatively interfering with their professional performance and personal relationships. Future studies focusing on strategies to ensure a better working condition for nurses are needed, seeking approaches aimed at providing better occupational health for workers.